Life cycle assessment (LCA) and energy assessment of the production and use of windows in residential buildings - Zbigniew Kowalczyk; Sebastian Twardowski; Mateusz Malinowski; Maciej Kuboń (Scientific Reports, 2023)
Abstract There is an observable scarcity of comprehensive research results comparing the environmental damage associated with both the production of windows and their subsequent operation. The environmental impact of the operation of windows depends on their thermal insulation parameters, and thus the amount of heat that must be generated to heat the building. The type of heating system and, above all, the type of fuel used to generate heat are also not without significance. Unfortunately, in Poland, a significant proportion of single-family houses operate on the fossil fuel heating system, including on coal and fuel oil. It is therefore important to present an environmental balance sheet of both the production and operation of windows for different variants of building heating. The purpose of the study was to determine: to what extent the manufacturing of windows of different construction and different insulation parameters affects the environment, to what extent does the negative environmental impact of the process of manufacturing with greater insulation compensate by the lower environmental impact related to savings on fuel (gas, coal, fuel oil) used to generate heat during the operation of windows. Three types of windows were selected for a detailed analysis: a triple-glazed aluminum construction, a double-glazed PVC construction and a triple-glazed PVC. The research results show that in the case of all impact categories, the greater environmental losses related to the improvement of the thermal insulation parameters of the windows at the production stage are fully compensated at the stage of their useful life, regardless of the type of fuel used to heat the buildings. Double-glazed PVC windows should be phased out of production due to significant environmental footprint associated with their operation.